Ties That Bind: The Impact of Multiple Types of Ties with a Customer on Sales Growth and Sales Volatility - Tuli, Kapil (Institutional Knowledge at Singapore Management University, 2010)
Suppliers in business-to-business settings are increasingly building a portfolio of multiple types of ties with individual customers. For example, in addition to supplying goods and services, a supplier may have a research-and-development alliance and a marketing alliance with a customer. This study investigates the effect of multiple types of ties with a customer on a supplier's performance with the customer. The findings from panel data on supplier-customer relationships suggest that an increase in the number of different types of ties with a customer results in an increase in supplier sales to the customer and a decrease in sales volatility to that customer. The effect of a change in relationship multiplexity (i.e., number of different types of ties) on the change in sales becomes weaker and its effect on the change in sales volatility becomes stronger as the competitive intensity in the customer's industry increases. The results also indicate that the effect of a change in the number of different types of ties on the change in sales volatility becomes stronger when the intangibles intensity in a customer's industry increases. The results are robust to alternative measures, alternative estimators, heteroskedasticity, and endogeneity, among other methodological concerns. These findings have clear implications for managing multiple types of ties with a customer and indicate that relationship multiplexity is a valuable nonfinancial metric.